Analisis Kemampuan Penulisan Huruf Kapital dan Tanda Baca Siswa Kelas IV Gugus I - Rustang Rustang; Rukayah Rukayah; Sidrah Afriani Rachman (Universitas Negeri Makassar, 2021)
This research is a quantitative descriptive study that aims to determine the ability to use capital letters and punctuation marks of class IV students of group I, Takkalalla District, Wajo Regency. The sample in this study were all fourth grade students in cluster I, Takkalalla District, Wajo Regency with a total of 56 students. The data collection technique used a validated test. Data analysis used descriptive statistical analysis and inferential statistics. The results showed that the average value of the use of capital letters was in the medium category and the average value of the use of punctuation was in the medium category. Meanwhile, for students who scored 75 on the use of capital letters, there were 24 out of 56 students (42.9%) and 34 out of 56 students (60.7%). The conclusion of this research is that the ability to write capital letters and punctuation marks of fourth grade students in Group I, Takkalalla District, Wajo Regency is under KKM.